Transurethral Surgical Anatomy of the Arterial Bleeder in the Enucleated Capsular Plane of Enlarged Prostates During Holmium Laser Enucleation of the Prostate - Choo, Min Soo (Korean Continence Society, 2014)
PURPOSE: To identify the endoscopic vascular anatomy of the prostate during Holmium laser enucleation of the prostate (HoLEP), and analyze the clinical risk factors associated with significant arterial bleeding. METHODS: We identified 107 consecutive patients with benign prostatic hyperplasia who underwent HoLEP between September 2009 and August 2010, performed by a single surgeon (S.J.O.). Two independent reviewers reviewed the surgery video database and completed a prespecified form. The location of bleeding arteries was marked at the level of the bladder neck, proximal prostate, distal prostate, and verumontanum. Arterial bleeding was classified into one of three grades according to bleeding severity (grades 2 and 3 indicate significant bleeding). RESULTS: The mean prostate volume was 65.1±31.5 mL, and the mean prostate-specific antigen (PSA) level was 3.69±3.58 ng/mL. During the HoLEP procedure, the most common locations of significant bleeders were the 2-5 and 7-10 o'clock positions in the proximal prostate. The average number of bleeding arteries was 12.1±7.9 per procedure, and 1.93±1.20 per 10 mL of prostate volume. Multivariate analysis revealed that prostate volume and serum PSA were significant parameters for estimating the number of bleeding vessels. CONCLUSIONS: During the HoLEP procedure, the most common locations of significant bleeders were the 2-5 and 7-10 o'clock positions in the proximal prostate. Prostate volume was associated with the number of bleeders. A careful approach to the capsular plane of the proximal prostate facilitates early hemostasis during the HoLEP procedure, especially with larger adenomas.